An overview on the phylogenetic classification of Brucella (2018)
ABSTRACT: The genus Brucella is a globally distributed intracelular pathogen that affects animals and humans and presents low genetic variability, which is a challenge for its phylogenetic reconstruction. Genus differentiation originally occurred due to its preference for a certain host and analyses throughout the years to classify the genus Brucella and its strains, depended on the techniques used, the number of strains or the methods of phylogenetic reconstruction. Its history goes from recognizing the entire genus as unique B. mellitensis species with multiple varieties, to recognizing more tan ten species. This review shows the journey through thetechniques that have been used to differentiate the genus Brucella, which, although they have generated clarity in the grouping of some species, still leaves doubts in related to the oldest species, their divergence and the type of grouping of the new species discovered. The application of newtechnologies such as phylogenomics is contributing to solve these questions.